Mediasi FOMO: Pengaruh Influencer dan Online Review terhadap Purchase Decision Produk The Originote - Fera Patrisya; Heriyadi; Nur Afifah; Juniwati; Bintoro Bagus Purmono (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
his study examines the influence of influencer marketing and online customer reviews on the purchase decision of The Originote products, as well as the mediating effect of FOMO on the purchase decision. This study involved 202 participants aged 17 to 35 years, who are aware of and have purchased The Originote products, and have seen influencer MaharajaSP reviewing and promoting The Originote products on TikTok. This study applied purposive sampling technique. Data was collected through an online questionnaire and analysis was conducted using SEM with SmartPLS 4 software. This study found that influencer marketing and online customer reviews significantly influence FOMO. Additionally, online customer reviews and FOMO significantly influence purchase decisions. However, influencer marketing does not have a significant impact on purchase decisions. FOMO acts as a mediator for the indirect influence of influencer marketing on purchase decisions. FOMO also mediates the indirect relationship between online customer reviews and purchase decisions. These findings provide insight into the factors that influence the purchase decision of The Originote consumers and practically offer insights for The Originote to develop the right marketing strategy